Using Maxwell's equation in vacuum, derive the wave equation for the x-component of the electric field vector associated with an electromagnetic wave
"\u200b\\overrightarrow{\\nabla}\\times\\overrightarrow{E}=-\\frac{\\partial \\overrightarrow{B}}{\\partial t }""\u200b\\overrightarrow{\\nabla}\\times\\overrightarrow{E}=-\\frac{\\partial \\overrightarrow{B}}{\\partial t }""\u200b\\overrightarrow{\\nabla}\\times\\overrightarrow{E}=-\\frac{\\partial \\overrightarrow{B}}{\\partial t }""\u200b\\overrightarrow{\\nabla}\\times\\overrightarrow{E}=-\\frac{\\partial \\overrightarrow{B}}{\\partial t }"
"\u200b\\overrightarrow{\\nabla}\\times\\overrightarrow{B}=\\mu_0\\epsilon_0\\frac{\\partial \\overrightarrow{E}}{\\partial t }"
"\u200b\\overrightarrow{\\nabla}\\times\\overrightarrow{B}=\\mu_0\\epsilon_0\\frac{\\partial \\overrightarrow{E}}{\\partial t }""\u200b\\overrightarrow{\\nabla}\\times\\overrightarrow{B}=\\mu_0\\epsilon_0\\frac{\\partial \\overrightarrow{E}}{\\partial t }""\u200b\\overrightarrow{\\nabla}\\times\\overrightarrow{B}=\\mu_0\\epsilon_0\\frac{\\partial \\overrightarrow{E}}{\\partial t }"
"\\overrightarrow{\\nabla}\\times\\overrightarrow{E}(x,t)\\overrightarrow{i}=\\begin{vmatrix} \\overrightarrow{i} & \\overrightarrow{j} & \\overrightarrow{k}\\\\ \\frac{\\partial }{\\partial x } & \\frac{\\partial }{\\partial y } & \\frac{\\partial }{\\partial z } \\\\ \\overrightarrow{E}(x,t) &0 & 0 \\end{vmatrix}=\\frac{\\partial E}{\\partial x }\\overrightarrow{j}"
"\\overrightarrow{\\nabla}\\times\\overrightarrow{B}(x,t)\\overrightarrow{j}=\\begin{vmatrix} \\overrightarrow{i} & \\overrightarrow{j} & \\overrightarrow{k}\\\\ \\frac{\\partial }{\\partial x } & \\frac{\\partial }{\\partial y } & \\frac{\\partial }{\\partial z } \\\\ 0 & \\overrightarrow{B}(x,t) & 0 \\end{vmatrix}=-\\frac{\\partial B}{\\partial x }\\overrightarrow{i}"
"\\frac{\\partial E}{\\partial x }=-\\frac{\\partial B}{\\partial t }"
"\\frac{\\partial B}{\\partial x }=-\\mu_0\\epsilon_0\\frac{\\partial E}{\\partial t }"
"\\frac{\\partial^2 E}{\\partial x^2 }=-\\frac{\\partial}{\\partial x }\\frac{\\partial B}{\\partial t }=-\\frac{\\partial}{\\partial t }\\frac{\\partial B}{\\partial x }=-\\frac{\\partial}{\\partial t }(-\\mu_0\\epsilon_0\\frac{\\partial E}{\\partial t })=\\mu_0\\epsilon_0\\frac{\\partial^2 E}{\\partial t^2 }"
"\\frac{\\partial^2 E}{\\partial x^2 }=\\mu_0\\epsilon_0\\frac{\\partial^2 E}{\\partial t^2 }"
Comments
Leave a comment